Towards Policy Decomposition for Autonomic Systems Governance by Applying Biologically Inspired Techniques - KEENEY, JOHN; WADE, VINCENT PATRICK (IEEE, 2008)
Policy-based management systems use declarative rules to govern their operation whilst satisfying the goals of the system. One of the fundamental issues in policy engineering remains the inability to automatically refine high-level goals to low level achievable goals, many of which will be interdependent and conflicting. This paper introduces the automated decomposition and refinement of management policies through the optimisation of balancing constraints by the innovative integration metaheuristic algorithms.
PUBLISHED
Keywords: Computer Science